Implementation of explicitly taught science of reading-based curriculum in a Spanish immersion K-3 classroom - Sheppard, Jennifer L. (My University, 2024)
The purpose of this study was to investigate how the teachers adjust and adapt to implementing a Science of Reading-based curriculum and how four Spanish Immersion (SPIM) English teachers have adapted to this new approach. This study took a close look at the K-3 Spanish Immersion classrooms in a suburban public school in a suburban town in DE. For this research, I used a qualitative case study methodology to critically evaluate how Spanish Immersion (SPIM) English teachers adapted and adjusted to a new SOR-based curriculum. I interviewed four teachers in grades K-3 who were teaching a scripted and prescribed SOR-based curriculum, Core Knowledge Language Arts (CKLA) by Amplify. The interviews took place three times throughout the winter and spring of the 2023-2024 school year. The two theoretical frameworks that will guide this study will be Bridges (1986, 2000) Transitional phases of managing organizational change and Rogers (1995) Diffusion of Innovations theory. This research investigated the following questions: 1.) In the context of implementing the Science of reading-based curriculum, how do Spanish Immersion teachers make meaning of using explicit, systematic, and structured literacy programs? 1.a.) How are Spanish Immersion teachers making sense of the SOR-based curriculum? 1.b.) How are Spanish Immersion teachers managing the challenges and changes of using a SOR-based curriculum? Initially teachers expressed feeling overwhelmed with the idea of letting go of their old curriculum and learning something new. As the year progressed and the teachers became more familiar with CKLA, they gained confidence and adjusted. The study suggested that teachers felt less apprehensive when they were provided with adequate professional development, time, and collaboration with colleagues to get used to the changes with the new curriculum. The teachers also began adjusting and supplemented where they felt necessary.
Keywords: Science of reading; Spanish immersion; Science of reading based curriculum; Elementary teachers adjusting to new curriculum